Nomophobia pada Mahasiswa yang Mengalami Digital Fatigue - Zulmi, Avrilia Mutiara; Ardi, Zadrian; Yendi, Frischa Meivilona; Fadli, Rima Pratiwi (Counseling and Humanities Review, 2025)
The increasing use of smartphones and the internet, especially among students who are susceptible to dependence on digital devices called nomophobia. Excessive digital exposure can also trigger digital fatigue. This study aims to describe the level of nomophobia in students who experience digital fatigue. The approach used is a quantitative method with descriptive analysis. The research sample was obtained through simple random sampling and purposive sampling techniques, with a total of 112 respondents. The instrument used was the nomophobia scale. Data analysis was carried out descriptively with the help of Microsoft Excel and JASP version 0.19.3.0. The results showed that the level of nomophobia in students who experienced digital fatigue was in the moderate category. These findings indicate that even though students experience digital fatigue, they still have difficulty controlling themselves when they cannot communicate, lose connections, cannot access information, and lose the comfort that is usually obtained from digital devices.